2022
DOI: 10.1007/s10796-022-10250-z
|View full text |Cite
|
Sign up to set email alerts
|

Technological Innovation, Sustainable Green Practices and SMEs Sustainable Performance in Times of Crisis (COVID-19 pandemic)

Abstract: COVID-19 restrictions significantly affected SMEs, which have faced many challenges to their sustainability within this fragile new environment. This study proposes a holistic framework of sustainable performance by interrelating factors showing robust associations to produce this effect' for achieving sustainable performance in SMEs, through integrating the Technology Organisation Environment (TOE) and Resource Based View (RBV) models, to test how sustainable green practices can process the TOE factors when a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 134 publications
3
37
0
Order By: Relevance
“…Before testing, in the adopted model, the variance inflation factor (VIF) test was conducted to avoid any possible mistakes caused by unnecessary correlations between the utilized latent constructs (Alraja et al. , 2022; Hair et al.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before testing, in the adopted model, the variance inflation factor (VIF) test was conducted to avoid any possible mistakes caused by unnecessary correlations between the utilized latent constructs (Alraja et al. , 2022; Hair et al.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Before testing, in the adopted model, the variance inflation factor (VIF) test was conducted to avoid any possible mistakes caused by unnecessary correlations between the utilized latent constructs (Alraja et al, 2022;Hair et al, 2010). All calculated values were less than 3.3 (Alraja, 2022;Hair et al, 2014), respectively (refer to Tables 1 and 5).…”
Section: Analysis Of Structural Modelmentioning
confidence: 99%
“…Thomas et al (2021) also explore the role of eco-innovation on the performance of organisations, considering the influence of stakeholders in establishing relationships between customers and suppliers. Finally, in Alraja et al (2022), it is further suggested that COVID-19 offers an opportunity for SMEs to have a more positive environmental stance and that this will be a contributing factor to better sustainable performance. The role of eco-innovation for SMEs is also evident,…”
Section: Eco-innovationmentioning
confidence: 99%
“…So, among well-scientists who determined green economy aspects approaches as well as community impact on global sustainability are Gunay, Kurtishi-Kastrati and Krsteska [7], Ngare, Otieno, Omwami, Ogutu, Opiyo, Gikonyo and Otieno [11], Söderholm [16]. Besides this, green entrepreneurship and small medium enterprise sustainable performance are considered in papers by Alraja, Imran, Khashab and Shah [2], Pangarso, 1126Pangarso, (2023 012010 IOP Publishing doi:10.1088/1755-1315/1126/1/012010 2 Sisilia, Setyorini, Peranginangin and Awirya [14]; Vasilescu, Dimian and Gradinaru [17]. It is also noteworthy that studies by Agrawal, Wankhede, Kumar, Upadhyay and Garza-Reyes [1], Montealegre and Iyengar [8]; Yixin, Maomao, Jing and Rui [19] aim to reveal the variability of different strategies to satisfy consumers changing the business model.…”
Section: Related Workmentioning
confidence: 99%